A case of heterozygous familial hypercholesterolemia requiring strict low-density lipoprotein cholesterol management with proprotein convertase subtilisin/kexin 9 inhibitor after coronary artery bypass grafting. Issue 3 (September 2021) - Abe, Takuro; Sato, Kayoko; Sekiguchi, Haruki; Nakao, Masashi; Im, Jihaeng; Sakai, Akiko; Yamamoto, Toshiyuki; Shoda, Morio; Hagiwara, Nobuhisa
Abstract : Heterozygous familial hypercholesterolemia (HeFH) is a common, autosomal dominant, genetic disease that results in premature atherosclerotic cardiovascular disease secondary to high-level low-density lipoprotein cholesterol (LDL-C) exposure. We present a 68-year-old male patient with HeFH who was diagnosed with acute coronary syndrome at 9 months after coronary artery bypass grafting, although his LDL-C level was decreased to 77 mg/dL from 213 mg/dL. The emergency coronary angiography revealed that all bypass grafts were occluded, and the large atherosclerotic plaque burden was observed even in right internal thoracic artery (RITA) by intravascular ultrasound examination. Emergency percutaneous coronary intervention (PCI) was performed to his RITA bypass graft. After strict LDL-C management with proprotein convertase subtilisin/kexin 9 (PCSK-9) inhibitors, re-stenosis was not observed at the PCI site and the atherosclerotic plaque burden in his graft drastically disappeared. The high-risk HeFH patients, including those suffering from coronary bypass graft stenosis despite receiving medical therapy, might need stricter management of lipid profile with PCSK-9 inhibitors. <Learning objective: Heterozygous familial hypercholesterolemia (HeFH) is one of the most common genetic disease causes of premature coronary disease. High-risk HeFH patients with multiple risk factors, including those suffering from coronary bypass graft stenosis despite receiving medical therapy, might need stricter management of lipid profile with proprotein convertase subtilisin/kexin 9inhibitors than that recommended in the guideline.>